2018
DOI: 10.1001/jama.2018.10359
|View full text |Cite|
|
Sign up to set email alerts
|

Fixed Low-Dose Triple Combination Antihypertensive Medication vs Usual Care for Blood Pressure Control in Patients With Mild to Moderate Hypertension in Sri Lanka

Abstract: anzctr.org.au Identifier: ACTRN12612001120864; slctr.lk Identifier: SLCTR/2015/020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(113 citation statements)
references
References 40 publications
1
96
1
5
Order By: Relevance
“…A 2018 trial of a fixed low-dose triple-combination antihypertensive drug tested in urban Sri Lanka, consisting of amlodipine, telmisartan, and chlorthalidone, showed substantial improvement in control of blood pressure compared with usual care at 6 months, and no difference in adverse events. 20 Another trial from 2016 showed that lowering LDL cholesterol with a high-potency statin was effective even among individuals only at intermediate risk of cardiovascular events. 21 Efforts to improve universal health coverage must directly address how these therapies can be delivered even more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…A 2018 trial of a fixed low-dose triple-combination antihypertensive drug tested in urban Sri Lanka, consisting of amlodipine, telmisartan, and chlorthalidone, showed substantial improvement in control of blood pressure compared with usual care at 6 months, and no difference in adverse events. 20 Another trial from 2016 showed that lowering LDL cholesterol with a high-potency statin was effective even among individuals only at intermediate risk of cardiovascular events. 21 Efforts to improve universal health coverage must directly address how these therapies can be delivered even more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…SPCs were exclusively used in only 34% of patients, while in the remaining 66% of patients the combinations used were either free (39%) or comprised both SPC and free components (27%). The use of SPCs, as compared to their free-drug counterparts, has been shown to be associated with a significant higher adherence rate to treatment [ 19 22 ] and lower health-care costs [ 20 ], while a non-significant reduction in blood pressure [ 19 ] but a significant improved blood pressure control rate [ 21 , 23 ] were reported. High adherence to antihypertensive treatment has been shown to be related to lower cardiovascular events [ 24 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fixed‐dose triplet combination therapy was not included in the present study, as it has only been in use since 2017. Recently, antihypertensive fixed‐dose triple combination therapy was shown to be well tolerated in Japan; and in Sri Lanka, it was reported to result in an increased proportion of patients achieving their target blood pressure goal versus usual care . It might be necessary to investigate fixed‐dose triplet combination therapy differences in hypertension treatment in future.…”
Section: Discussionmentioning
confidence: 99%